Stability of tetrapod breakwaters for different placing methods - Gürer, S; Çevik, E; Yüksel, Y; Günbak, AR (COASTAL EDUCATION & RESEARCH FOUNDATION, 2005)
The application of artificial armor units in the construction of rubble mound breakwaters is quite common. Various armor units such as the cube, the tetrapod, the dolos, and the quadripod are commonly used. Recent additions are the accropode and the core-loc, which can be used in a single layer of armoring. The stability of such breakwaters has subject of many studies to date. One area of interest has been the effect of the armoring unit placement method on the stability of breakwaters. The present study aims to compare two known methods of tetrapod placement in relation to breakwater stability. The results of the study are also reviewed in the light of earlier studies on breakwater stability.
Keywords: tetrapod; stability; breakwater; placement; Environmental Sciences & Ecology; Physical Geography; Geology